Study on the Protective Effect of Methyl Rosmarinate on Hypoxic Mice and Their Erythrocytes - Guo Q; Yin Z; Wang R; Sun Y; Zhao A; Yao W; Li W (Drug Design, Development and Therapy)
Qianwen Guo,1,2,* Ziyue Yin,1,2,* Rong Wang,1 Yuemei Sun,1 Anpeng Zhao,1 Wanteng Yao,1 Wenbin Li1 1Pharmacy of the 940th Hospital of PLA Joint Logistics Surpport Force, Lanzhou, People’s Republic of China; 2School of Pharmacy, Gansu University of Traditional Chinese Medicine, Lanzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenbin Li, Pharmacy of the 940th Hospital of PLA Joint Logistics Surpport Force, Lanzhou, People’s Republic of China, Email yfcs2002@163.comObjective: We have previously identified methyl rosmarinic (MR) acid as a 2.3-bisphosphoglycerate mutase (BPGM) activator. The present study aimed to verify the protective effect of MR on plateau field hypoxia mice and the mechanism of increased oxygen release capacity of erythrocytes in vivo.Methods: The anti-hypoxic effect of MR was investigated in a plateau field environment in Specific Pathogen Free -grade healthy BALB/c mice, male and female, and the effect of different doses of MR on the survival time of mice in confined space was investigated in an atmospheric pressure confinement hypoxia experiment, plasma inflammatory markers, oxidative stress indices of myocardial, brain, lung and liver tissues, as well as the histopathological damage and hypoxia in each experimental group were measured by HE staining and hypoxia probe method. Finally, the effects of MR administration to mice on the energy metabolic pathways and metabolites of erythrocytes in vivo were investigated.Results: After acute plateau entry in mice, the energy metabolic pathway of erythrocytes shifted to the glycolytic pathway as the duration of hypoxia increased. The administration of MR to hypoxic mice further activated Bisphosphoglycerate mutase (BPGM) and increased the levels of glyceraldehyde-3-phosphate and 2.3-bisphosphoglycerate (2,3-BPG), as well as further shifted glucose to the glycolytic pathway and further enhanced the activity of rate-limiting enzymes in the glycolytic pathway.Conclusions: MR activates BPGM in erythrocytes to produce more 2, 3-BPG from the glycolytic branch, thus exerting a protective effect against injury in hypoxic mice in the highland field. Keywords: erythrocytes, methyl rosmarinate, 2,3-biphosphoglyceric acid, hypoxia, glycolysis